ARTIFICIAL INTELLIGENCE IN THE CLASSROOM: INNOVATION OR DISRUPTION IN EDUCATION - Risqah Amaliah Kasman; Loso Judijanto; Elmiwati (Indonesian Journal of Education (INJOE), 2024)
These days, artificial intelligence (AI) is regarded as one of the most revolutionary technologies and consequently, its application is evident in various industries, education inclusive. The investigative design in this research utilizes review of literature. The analysis demonstrates that there are aspects that make it more reasonable to integrate artificial intelligence into the learning process, such as increased content diversity and student engagement, deep learning capabilities, and better organizational assistance. Fast and effective adaptive learning systems based on AI can provide appropriate materials and the required level of difficulty to each learner individually, while evaluation systems can automatically assess the knowledge and learning speed of students and relieve cut down the efforts needed by teachers. However, the study also suggests a number of barriers and possible risks, such as privacy issues or lack of privacy regarding students’ data, unfair treatment in AI algorithms, the gap of technology in society, and lack of human beings in the education process. The main point of this particular article is that AI as an ordinary classroom tool is both a source of creativity and a source of problems. The potential of technology to change the educational landscape is immense, but steps on how to achieve it should be gradual and ethical.